A comparison of skin and muscle for cortical revascularization - Porter, C. D.; Fowler, J. D.; Matte, G. G.; Johnston, G. H. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The purpose of this project was to compare the ability of skin and muscle to revascularize cortical bone segments in the canine distal limb. A model mimicking severe combined soft tissue and orthopaedic injury with bone devascularization involving the canine metatarsus was developed. Soft tissue defects were reconstructed with a reverse saphenous conduit flap or a free trapezius muscle flap. Cortical bone blood flow was determined by the radiolabeled microsphere method at 21 days post-reconstruction. In addition cortical porosity, the amount of fluorescent labelled intracortical new bone, and the maximum depth of periosteal new bone were determined. Significant differences were not detected between skin and muscle reconstructions for any of the measured parameters of cortical revascularization. The mean values for cortical bone blood flow were higher than expected from previous studies, and did not correlate with subjective assessments of adhesion quality between bone and reconstructive tissue onlay. The reverse saphenous conduit flap, and the free trapezius muscle flap, may respectively provide superior blood supply to underlying bone than local random pattern skin and local pedicled muscle. The reverse saphenous conduit flap has a robust and reliable vascular supply, unlike that to random pattern skin. The free transfer of muscle maintains a vigorous blood supply, and has shown improvements in blood flow over pedicled muscle. Blood flow to both tissue types may be favourably affected by the denervation associated with transfer, causing arteriolar vasodilation and reductions in vascular resistance. In this model, comparable revascularization of cortical bone at 21 days was seen beneath reverse saphenous conduit flaps and free trapezius muscle flaps. However, a role for endosteal revascularization cannot be excluded.Cortical revascularization by skin and muscle reconstruction was compared at 21 days in a canine metatarsal model. Significant differences in cortical bone blood flow were not detected
Keywords: Revascularization; muscle; skin; bone blood flow; bone; microvascular